Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Pelaku E-Commerce Di Indonesia (GEMA EKONOMI, 2023)
This study aims to test and analyze the factors that affect taxpayer compliance of e-commerce actors in Indonesia. The methods used in this study are quantitative descriptive methods and primary data using questionnaires. The sample from this study was 212 respondents who were a sample of e-commerce entrepreneurs in Indonesia. The technique in data collection uses simple random sampling by spreading research questionnaires in the form of google forms and then spread to personal chats or social media. The data preparation method in this study applies Smart PLS (Partial Least Square) software which is used to test hypotheses. The results showed that tax sanctions did not have a significant effect on taxpayer compliance, Digitalization of taxation had a significant effect on taxpayer compliance, Religiosity had a significant effect on taxpayer compliance and Religiosity was not proven to be able to significantly influence between the influence of tax sanctions and digitization on taxpayer compliance.